The relationship between organizational characteristics and capital structure in Malaysian firms - Rosli, Aizat Akmal; Ahmad, Kamilah; Mohamed Zabri, Shafie (American Scientific Publishers, 2018)
The determination of an appropriate capital structure of a firm is a critical financial decision for most business organizations for conforming to the firm’s objectives for the maximization of shareholders wealth and firm continuous sustainable growth. This study investigates an empirical issue which has received little attention in the literature; the determinants of capital structure among firms in developing countries. This study employs quantitative method to examine the determinants of the capital structure including asset tangibility, profitability, firm size, liquidity, and non-debt tax which may have significant associations with the firm capital structure. Data on characteristics of the organization and capital structure were collected from three financial period of a firm from a year 2013 until 2015. Sample of minimum 100 companies in consumer sector were retrieved from companies listed in Bursa Malaysia for gauging evidence on firms’ characteristics and capital structure. This study adds new empirical evidence to the body of knowledge by exploring the relationship between firm characteristics and capital structure from the perspectives of large firms in Malaysia.